Handbook of research on nurturing industrial economy for Africa's development - Nafukho, Fredrick Muyia; Makulilo, Alexander B. (Advances in electronic government, digital divide, and regional development., 2021)
"This book informs policymakers, investors, and practitioners on potential areas that may be relevant for nurturing the African countries' industrial economy in the African context and thus facilitating the fulfillment of the sustainable development goals (SDGs) and the African Union's Agenda 2063. The book helps scholars focus and rethink on the exact catalyst that will help nurture industrial economy for Africa"--